A life like mine - Rayner, Amanda; DK Publishing, Inc.; UNICEF (New York : DK, 2006)
Looks at what life is like for children of different countries and how each child can fulfill his or her hopes and ambitions no matter how little or much their human rights are infringed.
Includes index.
Library Media Connection starred.
Publisher's Weekly.
Wilson's Children.
6.8
3-6
Keywords: Children's rights -- Cross-cultural studies -- Juvenile literature; Children -- Cross-cultural studies -- Juvenile literature; Children; Children's rights; 23 Nisan; Children; Children's rights; World children